2023
DOI: 10.3390/antiox12010200
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin Attenuates Diabetic Cardiomyopathy by Inhibiting Oxidative Stress, Inflammation and Necroptosis via Sirtuin 3 Activation

Abstract: Dihydromyricetin (DHY), the main flavonoid component in Ampelopsis grossedentata, has important benefits for health. The present study aimed to investigate the exact effects and possible mechanisms of DHY on diabetic cardiomyopathy (DCM). Male C57BL/6 mice and sirtuin 3 (SIRT3) knockout (SIRT3-KO) mice were injected with streptozotocin (STZ) to induce a diabetic model. Two weeks later, DHY (250 mg/kg) or carboxymethylcellulose (CMC) were administrated once daily by gavage for twelve weeks. We found that DHY al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…It downregulates NF-κB expression through inhibition of IKK phosphorylation, the rate limiting step in NF-κB phosphorylation and activation. Moreover, DHM blocks the degradation of (IkBa) which is an inhibitor of NF-κB activation [41,42]. It is important to mention that, the upregulation of NF-κB and TNF-α expression in aortic tissues strongly matches the previously reported increase in their renal levels upon GTN administration.…”
Section: Discussionsupporting
confidence: 71%
“…It downregulates NF-κB expression through inhibition of IKK phosphorylation, the rate limiting step in NF-κB phosphorylation and activation. Moreover, DHM blocks the degradation of (IkBa) which is an inhibitor of NF-κB activation [41,42]. It is important to mention that, the upregulation of NF-κB and TNF-α expression in aortic tissues strongly matches the previously reported increase in their renal levels upon GTN administration.…”
Section: Discussionsupporting
confidence: 71%
“…Molecular docking showed a possible binding between DMY and the SIRT3 protein at the GLU-296, PRO-297, THR-257, GLN-260, THR-255, LYS-288, PRO-289, or ASP-290 sites, with a binding energy of −6.64 kcal mol −1 (Figure 1C). Murine chondrocytes exposed to IL-1𝛽 were treated with different concentration gradients of DMY to investigate its activation on SIRT3 in vitro according to the previous reports, [26][27][28] both at the transcriptional (Figure 1D) and translational level (Figure 1E,F) and without compromising cell viability (Figure S1A, Supporting Information). We observed that the agonism of SIRT3 by DMY not only promoted cartilage ECM anabolic metabolism (collagen type II, COLII and aggrecan, ACAN) but also restrained the degradation activities of collagenases (matrix metalloproteinase 13, MMP13) and proteoglycanases (ADAM metallopeptidase with thrombospondin type 1 motif 5, ADAMTS5) (Figure 1H,I and Figure S1B,C, Supporting Information).…”
Section: Activation Of Sirt3 By Dmy Protected Cartilage Ecm Anabolic/...mentioning
confidence: 99%
“…Currently, there is limited basic research on natural product treatments targeting necrotic apoptosis, and further studies should be conducted to explore effective drugs for targeting necrotic apoptosis in the treatment of DCM. Chen et al (Chen et al, 2023) found that DHY can alleviate high glucose‐induced cardiac dysfunction, myocardial fibrosis, and cardiac remodeling in male C57BL/6 mice model. In vitro and in vivo experiments, DHY reduced the production of superoxide and mitochondrial oxidative damage in cardiac cells and inhibited the expression of IL‐1β and NLRP3, indicating that DHY alleviated oxidative stress and inflammation in DCM.…”
Section: Natural Substances Treat Dcm By Targeting Different Pcdsmentioning
confidence: 99%